Electrocoagulation Process to Reduce Microplastic in Wonokromo Surface Water - Firra Rosariawari; Tuhu Agung Rachmanto; Mohamad Mirwan; Dila Rahmayanti (Future Science)
The abundance of microplastics in Surabaya's surface water can disrupt the sustainability of river ecosystems and harm humans because most of the raw water used by the people of Surabaya comes from surface water. Microplastics less than 5µm in size contain harmful chemicals such as Polychlorinated Biphenyls (PCBs) and are toxic. One alternative treatment is to reduce the levels of microplastics in the electrocoagulation process. Electrocoagulation is the process of clotting and deposition of fine particles in water using electrical energy. Microplastics contained in the water are removed through flocculation and deposition processes. This study aims to determine the effectiveness of the electrocoagulation process on reducing microplastic levels. The variables of this experiment are the distance of the electrodes (1.5 cm, 2 cm; 3 cm, and 5 cm), and the detention time (15 minutes, 25 minutes, 30 minutes, 45 minutes). This research was set up by using a reactor with a volume of 5 liters and a settling time of 30 minutes.